Gender and age related features of metabolically healthy obesity phenotype prevalence - S. V. Mustafina; D. A. Vinter; L. V. Shcherbakova; S. K. Malyutina; Y. I. Ragino; O. D. Rymar (Бюллетень сибирской медицины)
Aim. The study objective was to assess the age and gender characteristics of the metabolically healthy obesity phenotype (MHO) prevalence, taking into account various classifications.Materials and methods. The materials used are the cross-sectional studies of the population cohort (Health, Alcohol and Psychosocial factors in Eastern Europe (HAPIEE) project, Novosibirsk), with the total of 3,197 people, among them 857 men (26.8%) and 2,340 women (73.2%), with BMI ≥30 kg/m². The MHO is defined according to different classifications: 1. IDF (International Diabetes Federation, 2005) – Waist circumference (WC) ≥ 94 cm in men and ≥80 cm in women and one or none of the components of metabolic syndrome (MS); 2. NCEP ATP III (the National Cholesterol Education Program Adult Treatment Panel III, 2001) in the presence of 2 and / or less components of the metabolic syndrome and 3. RSC (The Royal Society of Chemistry) – the index of waist circumference / hip circumference (WC / HC) ≤0.9 in men and ≤0.85 in women.Results. According to IDF the frequency of MHO in the group was 23.2%; NCEP ATP III – 41.8; RSC criteria – 27.1%. The frequency of MHO was higher in women than in men, and it significantly decreased with the age in women population. In all classifications, increased average blood pressure (BP) level, with normal average values of the level of triglycerides (TG) and high-density lipoprotein (HDL) is typical for persons with MHO. The surveyed according to the RSC criteria people with MHO demonstrate higher frequency levels of all cardio metabolic risk factors than those surveyed with the use of other criteria of MHO.Conclusion. The frequency of MHO varies depending on the used classification. In women, the frequency of MHO is reliably higher than in men. With the age, a significant reduction of the frequency of MHO in women is manifested. The frequency of arterial hypertension and abdominal obesity, the level of fasting blood glucose and LDL (low density lipoprotein), hypertriglyceridemia is higher in persons with MHO according to the criteria RSC.